Revitalisasi Perlindungan Anak Dan Perempuan Menuju Pembangunan Berkelanjutan (Sustainable Development Goals) - Fransiska Novita Eleanora; Lusia Sulastri (Universitas Widya Gama Malang, 2020)
The purpose of this study is to determine the revitalization of protection for children and women towards sustainable development or what is known as the sustainable development Goals. The protection referred to here is the protection of the fulfillment of the rights of children and women which must receive attention because it is very vulnerable to all actions such as discrimination as well as violence which can lead to violations of the rights to the lives of children and women where the violation is a crime or an act. criminal. Protection towards sustainable development gives attention and focus to the lives of children and women in order to obtain fulfillment and protection of their rights, both of which the most important rights are related to education to right and teaching, to obtain health, as well as to get proper housing and not be treated. arbitrarily by anyone and entitled to justice and equality of rights. Problem formulation, namely how to revitalize the protection of men and women towards sustainable development. The research method used is juridical normative research, which is an approach based on the main legal materials based on existing concepts, theories, legal principles and legislation related to this research. The result is that sustainable development can be realized if there is cooperation and coordination between various parties including the community to always pay attention and care for the protection of children and women.